2008
DOI: 10.1063/1.2970043
|View full text |Cite
|
Sign up to set email alerts
|

Using metal-insulator-semiconductor structures to investigate dielectrics charging in capacitive microelectromechanical switches

Abstract: Capacitance-voltage characteristics measured on metal-insulator-semiconductor structures are used to investigate dielectrics charging in the capacitive microelectromechanical switches. An analytical model based on this method has been established. Effects of electrical stress on charge accumulation in silicon-rich nitride were experimentally investigated. The charging parameters of the silicon-rich nitride were extracted by the exponential curve fitting method. The experimental results show that three main phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Different narrow-band and wide-band phase shifters are reported in the literature [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Reflection type phase shifter is reported with an average insertion loss and phase error of 3.5 dB and 4.9°, respectively, over 15-45 GHz [6].…”
Section: Introductionmentioning
confidence: 99%
“…Different narrow-band and wide-band phase shifters are reported in the literature [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Reflection type phase shifter is reported with an average insertion loss and phase error of 3.5 dB and 4.9°, respectively, over 15-45 GHz [6].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of phase shifters have been reported in the literature over last two decades [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] in narrowband or wideband. One of the major challenges of a wideband phase shifter is to track any frequency over a wide spectrum without compromising other performances like loss, matching, and phase error.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the MIS structure should be a better model for investigating the charge relaxation of dielectrics in capacitive micro-actuators. In our previous paper [9,10], the analytical model based on MIS structure has been established for modeling the dielectrics charging in the RF MEMS switches, the experimental results demonstrated that the model is helpful for the quantitative analysis of dielectrics charging and discharging in RF MEMS switches.…”
Section: Introductionmentioning
confidence: 99%